Experimental studies on premixed charge and reactivity-controlled compression ignition combustion modes using gasoline/diesel fuel combination. (November 2022) - Sankaralingam, Ram Kishore; M, Feroskhan; M, Elango; Yunus Khan, T.M.; Javed, Syed; Baig, Rahmath Ulla; Thangavel, Venugopal
Abstract: Homogeneous charge compression ignition (HCCI) is a promising technology to reduce NOx and soot emissions in compression ignition (CI) engines. However, this technology lacks combustion control to circumvent the knocking and misfire limitations. Premixed charge compression ignition (PCCI) and reactivity-controlled compression ignition (RCCI) are techniques that use partial homogeneous charge to reduce NOx and soot emissions. Here, combustion is regulated either by controlling the injection timing or fuel reactivity. PCCI uses a part of fuel as premixed to form a partially homogeneous charge and the rest as direct-injected. RCCI, on the other hand, uses a low reactive fuel (LRF) for port injection to form a partially homogeneous charge and a high reactive fuel (HRF) for direct injection. In this work, we studied PCCI and RCCI modes using commercially available fuels like diesel and gasoline, and we compared the results with diesel baseline operation. Adding 40% (by weight) heated diesel port injection to normal diesel operation in PCCI mode at different loads showed a minimum reduction in NOx and smoke emissions by 15% and 6%, respectively, when compared with diesel baseline. This mode was found to be equally efficient with diesel baseline operation at low torque conditions. Similarly, adding 40% (by weight) of gasoline port injection to normal diesel operation in RCCI mode at different loads showed a minimum reduction in NOx and smoke emissions by 20% and 14%, respectively, when compared with diesel baseline. This mode was found to be equally efficient with diesel baseline operation at high torque conditions.